Asas Keadilan Pemungutan Pajak dalam Peraturan Pemerintah No 23 Tahun 2018 Tentang Pajak Penghasilan - Made Dwi Surya Suasa; I Made Arjaya; I Putu Gede Seputra (Warmadewa Press, 2021)
In mid-2018, the government issued new regulations in the field of taxation which is expected to be an increadible impact for tax revenues. The rules are set out in the Government Regulation Number 23 Year 2018 regarding Income Tax on Income Effort Received or Provided Taxpayers Who Have Specific Gross Distribution (Government Regulation Number 23 Year 2018). Various responses from the community came after the release of the Government Regulation. One is the aspect of fairness in the taxation of income that seems to be ruled out with the advent of the Government Regulation. The principle of fairness in income tax collection adheres to vertical equity, the higher the income (net) earned or received by the higher taxes that are owed. Vertical Justice not accommodated in the regulation is to make the basis for the calculation of gross turnover tax payable. As a result, taxpayers who have the same gross turnover is considered to have the same economic additional capabilities. Estuary of the principle of vertical equity is a theory that emphasizes the style bear minimum cost of living.